The Anxiety of Lung-TB Patients Consuming Medicine more than 6 Months - Maria V. B. Aty, Yoany; Making, Maria Agustina; Yubilianti, Yohana Jesica Daliman; Gonsalves, Dominggos; Blasius, Gadur (JURNAL KESEHATAN PRIMER, 2022)
Introductions: Treatment for pulmonary TB requires a long period of time, at least six months of taking medication. The impact of this long process results in saturation of pulmonary TB patients to complete their treatment program. This condition increases the patient's anxiety about the timeliness of taking medication regularly. This study aims to describe the level of anxiety of pulmonary TB patients while taking TB drugs for a period of more than 6 months in the working area of the Bakunase Health Center. Methods: This is a descriptive study with a cross sectional design approach. The sampling technique was total sampling with a total of 53 pulmonary TB patients. The research instrument used was the Zung Self-Ratining Anxiety Scale (SAS/SRAS) questionnaire. Descriptive statistical test analysis. Result: The results showed that the characteristics of pulmonary TB patients at the Bakunase Health Center were mostly 26-35 years old as many as 13 people, 28 women, 41 people with 6-12 months of treatment, housewives/not working and self-employed as many as 13 people, and 19 people have high school/high school education. The level of anxiety that occurs in pulmonary TB patients while taking TB drugs for a period of more than 6 months in the work area of the Bakunase Health Center has an average value of 46.83 with the highest value of 69 and the lowest being 27, pulmonary TB patients experience a mild level of anxiety. Conclusion: Characteristics of respondents based on age, gender, length of treatment, education, and occupation of pulmonary TB patients are factors that influence the level of anxiety. keywords: Kecemasan; pengobatan tuberkulosis; tingkat kecemasan; tuberkulosis